Introduction to the nervous system - Andrews, Melissa R. (Henry Stewart Talks, 2019)
Functions of the nervous system, Building blocks of the nervous system, Areas and divisions of the nervous system, Autonomic nervous system, Neurons as excitable cells, Resting membrane potential and action potentials, Neuronal communication and synaptic transmission, Propagation of signals and myelination